The Scope of Artificial Intelligence in Evidence Evaluation in Judicial Proceeding - Shehroze Ali Akbar; Tabinda Mehdi; Seemab Azam (`, 2025)
The integration of artificial intelligence (AI) into judicial evidence evaluation represents a significant shift in modern legal systems, driven by increasing volumes of digital evidence and the need for efficient, consistent analysis. This article examines the scope of AI in evidence processing within judicial proceedings, with a focus on Pakistan’s legal landscape. It explores AI applications such as natural language processing, predictive analytics, and pattern recognition, which enhance document review, case management, and decision-support systems. Through a mixed-methods approach combining quantitative surveys of legal professionals and qualitative content analysis, the study assesses AI’s impact on trial efficiency, ethical considerations, and systemic biases. Findings indicate that AI improves speed and accuracy in evidence handling but also introduces challenges related to transparency, fairness, and data privacy. The research highlights the tension between technological advancement and judicial accountability, advocating for human-centric, ethically guided AI integration. Recommendations include governance frameworks, explainability mechanisms, and capacity-building initiatives to ensure responsible adoption. The study concludes that AI serves as an augmentative tool rather than a replacement for judicial judgment, offering transformative potential if implemented with robust safeguards. Keywords: Artificial Intelligence, Judicial Proceedings, Evidence Evaluation, Legal Technology, Predictive Analytics, Ethical AI, Pakistan Judiciary, Digital Evidence, Bias in AI, Legal Reform